ISO 14001 environmental certification step by step - Edwards, A. J. (Antony John), 1940- (Oxford ; Burlington, MA : Elsevier Butterworth-Heinemann, 2004)
The do-it-yourself manual, with steps to success and simple explanatory notes, designed for real companies. ISO 14001 Environmental Certification Step by Step has been written with smaller companies especially in mind. Dr. A.J. Edwards explains how to achieve the ISO 14001 standard aided by resources freely available from the accompanying website, including a sample manual and detailed sample registers and procedures. Together, these provide a quick and straightforward guide to achieving the requirements of ISO 14001 Environmental Certification. This revised edition has been updated to cover the latest developments in the interpretation of the standard, plus changes in related legislation, such as the EU's Eco-Management and Audit Scheme (EMAS), Control of Pollution regulations, Dangerous Substances and Explosive Atmospheres Regulations, Landfill charges, Pollution Prevention and Control, and Asbestos Regulations. In addition, the new ISO 19011:2002 standard for auditing is reflected in the book, as are approaches to phased introduction of ISO 14001. Many organisations working towards ISO 14001 already possess ISO 9000 registration, or choose to achieve ISO 14001 and ISO 9000 simultaneously as an integrated system. To prevent duplication, ISO 14001 Environmental Certification Step by Step includes cross-referencing of ISO 14001 requirements to the relevant procedures in the Quality System. * A do-it-yourself manual, with steps to success and simple explanatory notes * Revised and updated to cover developments in the interpretation of the standard, changes in related legislation, such as the EU's Eco-Management and Audit Scheme (EMAS), new standards and standards * Supported by downloadable forms and procedures.
Introduction to environmental management -- The global perspective -- Brief history of environmental standards -- Introduction to ISO 14001 -- Planning the project -- Policy and planning -- Implementation and operation -- Checking, corrective action and management review -- The Environmental Management Manual (step 7) -- The launch (step 8) -- Internal environmental auditing (step 9) -- Assessment (step 10) -- EMAS -- Final thoughts -- Appendix A: briefing notes for toolbox talks -- Appendix B: aspects checklist -- Appendix C: regulations checklist -- Appendix D: useful information -- Appendix E: UKAS accredited environmental certification bodies -- Appendix F: glossary -- Registers of environmental aspects and environmental information -- Operating procedures -- Environmental Management Manual.
Includes index.
Keywords: ISO 14000 Series Standards; Environmental protection -- Standards; Production management -- Environmental aspects; Electronic books